A CPW‐fed broadband circularly polarized wide slot antenna with modified shape of slot and modified feeding structure. Issue 6 (June 2016) - Chen, Zhe‐Feng; Xu, Bo; Hu, Jun; He, Sailing
ABSTRACT: A low‐profile, compact, concisely designed CPW‐fed broadband circularly polarized wide slot antenna is proposed. By protruding the ground into the wide slot, the distribution of equivalent magnetic currents inside the slot is changed. Together with appropriate adjustment of the feeding structure, broad impedance bandwidth and broad axial ratio bandwidth (ARBW) can be achieved simultaneously. General design steps are given so that the antenna can be easily transplanted to other bands. The measured results show that the 3 dB ARBW is 1.85–3.15 GHz (52%) and the impedance bandwidth is 1.35–4.12 GHz (101.3%). Detailed design procedures and key parameters analysis are also given for further understanding of the antenna design. © 2016 Wiley Periodicals, Inc. Microwave Opt Technol Lett 58:1453–1457, 2016